Hydration and perceptual responses resulting from a training session involving female rhythmic gymnastics athletes - Detoni Filho, A.; Reimann Baptista, R.; Guiramand, G.; Lague Sehl, P.; Tomedi Leites, G. (Journal of Exercise, Sport & Orthopedics, 2014)
Young rhythmic gymnastics (RG) athletes engage in long training sessions that can lead to dehydration, especially on very hot days. Hydration status can affect the sporting performance and health maintenance of these young gymnasts. To evaluate the sweat volume, fluid balance and perceptual responses of young female RG athletes during a training session in the heat, fourteen female RG athletes (11.3±2.6 years) with a body fat percentage of 17.35±4.85% participated in this study. Body weight was measured and a urine sample collected for color analysis, both before and after the training session. The workout lasted 2.5 h in environmental conditions of between 29 oC and 50% relative humidity (RH), and 30 °C and 59% RH. Water was made available for consumption ad libitum and sweat volume was calculated from the change in body weight, corrected for water intake. The rate of perceived exertion, thermal sensation, thermal comfort, and irritability were measured every 30 minutes using categorical scales. Sweat volume was 1146.6±412.6 mL and water consumption was 825.2±368.1 mL. The negative fluid balance was between 1-2% in 50% and 1% in 42.8% of the athletes. Twelve athletes began the training session hypohydrated (urine color between 3 and 7), and 92.3% were hypohydrated after training (urine color between 4 and 6). There was an increase in thermal sensation (8±1) and discomfort (3±1) over the course of the workout. The RG athletes were unable to adequately replace their fluid losses, despite water being available for drinking ad libitum, which may reflect on the perceptual responses to heat.